PENGARUH MOTIF MENONTON PROGRAM ACARA MATA LENSA ANTV TERHADAP KEPUASAN INFORMASI FOTOGRAFI KOMUNITAS FOTOGRAFI PEKANBARU - Muhammad Fauzan; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Mass Media has a huge influence on the direction of public life, as understood in the mass media itself that the media specifically designed to reach a very broad community. Type media itself has traditionally are newspapers, magazines, radio, and television. Entertainment media needs of the audience will be as fulfilled by the existence of the shows that are presented by the mass media. In accordance with the uses and gratification theory which explains about the freedom in choosing which media audiences are considered to be able to meet their needs after consuming media. Where in theory there are concepts of measuring satisfaction Sought is Gratification (Motif) and Gratification Obtained (Satisfaction). Sought gratification is the background of a person's motive to used media, while Gratification Obtained is a real satisfaction obtained after using media.The purpose of this research is to determine how much influence the motive watch quiz program on the Mata Lensa ANTV Komunitas Fotografi Pekanbaru as an information satisfaction. The method used in this research is quantitative method with a survey of explanation, the researchers collected data using questionnaires. The location of this research is in the Community Photography Pekanbaru. The total sample for this study of 37 respondents who watched the program Mata Lensa ANTV. To find out how much the relationship between the two variables, the researchers use Person Product Moment correlation analysis. As for the questionnaire data processing, done using Statistics Program Product Of Service Solution (SPSS) Windows version 17. These results indicate that the influence of motive watch quiz program on the Mata Lensa ANTV Komunitas Fotografi Pekanbaru as an information satisfaction, that the value of R = 0.603 and the coefficient of determination (Rsquare) is approximately 0,363 result of squaring the correlation coefficient of 0.603 x 0.603 with 0.001 significance level of less than α = 0.05. The figure shows the understanding that the contribution of the effect of the use upon the satisfaction motif variables obtained amounted to 36.3% with a weak category. Keywords: Mass Media, Entertainment, Theory Uses And Gratifications, Motif, Satisfaction, Mata Lensa ANTV